TECHNO-ECONOMIC ANALYSIS OF CHILI SAUCE PRODUCTION USING FERMENTED CASSAVA FLOUR - Rahim, Abdul; Adi, Qadaruddin Fajri; Adelina, Fitrah; Sudarmin (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
This study performs a techno-economic analysis to assess the feasibility of developing chili sauce products incorporating fermented cassava flour as a local food ingredient. The evaluation covers both technical/technological and economic aspects. Technologically, the product exhibits favorable characteristics with a mean moisture content of 72% and pH of 4.01, supported by positive organoleptic test results. Economically, financial analysis indicates strong viability, with a Net Present Value (NPV) of IDR 40,138,730 an Internal Rate of Return (IRR) of 34.53%, a Benefit-Cost (B/C) Ratio of 2.25, and a Payback Period (PP) of 2 years and 1 months. The integrated findings from both technical and economic evaluations confirm that chili sauce formulated with fermented cassava flour is technically sound and economically feasible for commercial development. This product has significant potential to enhance added value, create new business opportunities, and support sustainable local food security. keywords: chili sauce, techno-economic, cassava